An optical performance comparison of three concentrating solar power collector designs in linear Fresnel, parabolic trough, and central receiver. (1st December 2018) - Kincaid, Nicholas; Mungas, Greg; Kramer, Nicholas; Wagner, Michael; Zhu, Guangdong
Highlights: Unique aspects of three different CSP collector designs are identified. Central receiver technology is most sensitive to the solar field optical errors. Both latitude and annual solar irradiation are critical in the plant site selection. Abstract: The optical performance of a concentrating solar power (CSP) collector is critical to the overall efficiency of the system. This study presents a detailed optical comparison between three representative CSP collector designs including linear Fresnel, parabolic trough, and central-receiver technologies. Optical models are implemented in SolTrace, which is ray-tracing software developed at the National Renewable Energy Laboratory. The ray-tracing algorithm is used to calculate a collector's design-point performance as well as its incidence-angle modifiers to evaluate the collector performance at any sun position during a typical meteorological year. The efficiency over a one-year period is then analyzed based on ray-tracing results. Using China Lake (California) as an example, the annual optical efficiency is 60% for the selected parabolic trough collector, 52% for the selected central-receiver technology, and 40% for the selected linear Fresnel collector. The parabolic trough has the highest optical performance among all. The selected central-receiver technology provides the most consistent seasonal production profile over the course of the year due to its two-axis-tracking ability but would suffer most from the increasing solar collector optical error. It is also shown that a dramatic cost reduction is required for the selected linear Fresnel technology to be competitive in the future energy market. Sensitivity of three CSP technologies to the deployment locations and the overall optical-error magnitude is also examined through annual performance analysis. The results will provide insights into a better understanding on inherent technical aspects of different CSP technologies.